Research and Application of Urban Rail Transit Train Collision Performance - SU Qiang; WANG Huijuan; SHEN Xukui; JI Mengnan; LIU Yang (Chengshi guidao jiaotong yanjiu)
［Objective］ In order to effectively reduce the hazards from the collision of urban rail transit trains and thereby improve the safety of train operation, it is necessary to conduct research on the collision performance of urban rail transit trains during the operation process. ［Method］ Based on urban rail transit train collision scenarios and standards，a train collision energy management scheme is proposed. The finite element software is utilized to conduct simulation calculation of train collision scenarios, the speed, vehicle interface force, coupler force, vehicle deformation amount, stress and strain in trains collision are analyzed. ［Result & Conclusion］ During the collision with the train speed of 25 km/h, the maximum deformation in the passenger area of the vehicle would occur in Car 6. This elastic deformation could reach 12.2 mm, far less than that specified in EN 15227:2008+A1:2010 Railway applications-Crashworthiness requirements for urban rail transit vehicle bodies . The maximum plastic strain of the vehicle occurring at the ends of Car 6 is 4.7%, less than 10% as specified in EN 15227:2008+A1:2010. Therefore, the vehicle meets the requirements for the survival space specified in EN 15227:2008+A1:2010 during the collision. The maximum lifting height of the wheelset at the rear bogie of Car 5 reaches 10.5 mm, not exceeding 75% of the flange height, thereby without the risk of vehicle climbing. The proposed collision energy management scheme satisfies the requirements for vehicle crashworthiness in EN 15227:2008+A1:2010.